2017
DOI: 10.11607/prd.2765
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Periodontal Response to Anterior All-Ceramic Crowns with Either Chamfer or Feather-edge Subgingival Tooth Preparations: Six-Month Results and Patient Perception

Abstract: Subgingival margins are often required for biologic, mechanical, or esthetic reasons. Several investigations have demonstrated that their use is associated with adverse periodontal reactions, such as inflammation or recession. The purpose of this prospective randomized clinical study was to determine if two different subgingival margin designs influence the periodontal parameters and patient perception. Deep chamfer and feather-edge preparations were compared on 58 patients with 6 months follow-up. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 26 publications
1
25
0
4
Order By: Relevance
“…Gingival margin changes have been associated with fixed prosthodontic procedures 80,81,83–90 . They can be linked to a variety of factors, including crown preparation and margin position, 80,91–93 gingival displacement and impressions, 81,84,94 provisional prostheses, 95 and luting agents 96…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingival margin changes have been associated with fixed prosthodontic procedures 80,81,83–90 . They can be linked to a variety of factors, including crown preparation and margin position, 80,91–93 gingival displacement and impressions, 81,84,94 provisional prostheses, 95 and luting agents 96…”
Section: Resultsmentioning
confidence: 99%
“…Limited comparative evidence related to periodontal outcomes of different finish line designs is however available, generally showing only minor differences for BoP and recession 91,92 …”
Section: Resultsmentioning
confidence: 99%
“…The technique eliminates the tooth's anatomical crown emergence at the cementoenamel junction (CEJ) to make room for the creation of a new emergence profile by the prosthetic crown. At the same time, rotary curettage of the gingival sulcus is performed [24][25][26][27][28]. The technique was inspired by periodontal prosthetic protocols of the 1980s and 1990s, such as rotary curettage and knife-edge dental preparation [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that dental preparation and the exact position of the prosthetic crown are not related. Although the reshaping, of tissues includes connective tissue, the prosthetic crown will be positioned according to the biological position of the cementoenamel junction, 0.5-1 mm from the gingival margin [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…17,30,31 Some evidence suggests a knife-edge or feather-edge margin may be associated with less gingival recession, but more bleeding on probing. 32,33 The knife-edge preparation was frequently correlated with minimally invasive crown preparations. 34 Studies have shown that a clinician's gender is associated with treatment decisions and outcomes.…”
Section: Discussionmentioning
confidence: 99%